Rethinking Multicultural Group Work as Intercultural Learning. (July 2017) - Reid, Robin; Garson, Kyra
This article presents our findings of an exploration of students' perceptions of multicultural group work when specific changes in pedagogy and methods of evaluation were made to include the processes students navigate, instead of merely the end product of their collaboration. Shifting demographics and increasing cultural diversity in higher education classrooms have presented the need for educators to rethink the formation, preparation, and evaluation of group work. This paper argues for learning to include the process of working with others rather than merely the product of group work. The findings from this study support previous literature advocating for more intentional approaches by providing evidence that changes to the preparation of groups, the formation of groups, and the evaluation of group work enhanced intercultural learning and improved the experience of working in a multicultural group for the majority of the participants.